De novo 6.9 Mb interstitial deletion on chromosome 4q31.1-q32.1 in a girl with severe speech delay and dysmorphic features. - Fabretto, Antonella; Santa Rocca, Maria; Perrone, Maria Dolores; Skabar, Aldo; Pecile, Vanna; Gasparini, Paolo (Am J Med Genet A, 2012)
Deletion of the terminal part of long arm of chromosome 4 is a condition characterized by facial dysmorphisms, cardiac and limb defects, and developmental delay. Deletions usually involve the terminal part of the chromosome and most frequently are interstitial. Here, we report a de novo interstitial deletion resulting in a microdeletion of 6.9 Mb involving 4q31.3-q32.1 segment, detected by SNPs-Array technique in a 4-year-old female showing severe speech delay, mild facial dysmorphisms, and joint laxity. Phenotype-genotype relationships looking at the genes involved in this part of the chromosome were also carried out and data compared with those previously described.
Keywords: Abnormalities, Multiple; Child, Preschool; Chromosome Deletion; Chromosomes, Human, Pair 4; Developmental Disabilities; Female; Genotype; Humans; Language Development Disorders; Phenotype; Sequence Deletion